Description of two new species of Rhaphidophora (Orthoptera: Rhaphidophoridae: Rhaphidophorinae) from Yunnan, China - Yu, Tingting; Liu, Mingyu; Bian, Xun; Zhang, Bin (Zootaxa, 2025)
This paper describes two new species of Rhaphidophora from Yunnan, China. The illustrations, descriptions and diagnosis are provided based on the specimens deposited in Guangxi Normal University. The two new species have distinctive male epiprocts.